Representation of Laila’s Hierarchy of Needs through Speech Acts in Nizami Ganjavi’s Majnun Layla - Alawy , Ahmad; Hidayatullah, Moch Syarif (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Literary works not only represent linguistic aesthetics but also portray the psychological conditions of characters through dialogues and social relations within the story. This study aims to describe illocutionary and perlocutionary speech acts, as well as the psychological condition of Laila in Nizami Ganjavi’s Majnun Layla, based on Abraham Maslow’s hierarchy of needs theory. This research employed a descriptive, qualitative method, drawing on pragmatics and psychological approaches in literature. The data consisted of dialogues and utterances from the fourth chapter of the novel, collected through observation and note-taking. The data were analyzed using the pragmatic equivalent method and Miles and Huberman’s analysis model through the stages of data reduction, data display, and conclusion drawing. The findings revealed that the illocutionary speech acts identified in the novel include assertive, expressive, and directive acts. In contrast, perlocutionary acts appeared through emotional responses such as anger, threats, sadness, and psychological pressure among the characters. Based on Maslow’s hierarchy of needs, Laila’s psychological condition is dominated by safety, belonging and love, and self-esteem needs. These needs are not fully fulfilled due to social pressure, separation from Qays, and family domination over Laila’s life. This study demonstrates that speech acts in literary dialogues function not only as communication tools but also as representations of psychological conflicts and social relations within literary works.